Fabrication of TiO2 photocatalytic electrode and contamination control with atmospheric pressure O2 plasma jet. Issue 2 (5th July 2019) - Song, Chan‐Geun; Kim, Tae Hwan; Yoon, Jong‐Won; Lee, Ho-Jun; Won, Jonghwan; Lee, Seung Whan
Abstract: In this study, we demonstrate the fabrication of TiO2 photocatalytic electrode by sol‐gel and electrospinning technique. The anatase TiO2 nanofiber is successfully formed after thermal annealing at 260°C. As‐prepared TiO2 photocatalytic electrode contains surface contamination, which includes a polymer binder such as ethyl cellulose, carbon by carbonization of polyvinylpyrrolidone, and residue polyvinylpyrrolidone. To efficiently remove the surface contaminants from the TiO2 photocatalytic electrode, we employ an atmospheric‐pressure O2 plasma jet and the exposure time is controlled by the scanning rate. As the results, photodegradation efficiency of methylene blue is significantly enhanced with a scanning rate in the range of 100‐500 μm/s and was saturated with a scanning rate in the range of 10‐100 μm/s. Abstract : The atmospheric‐pressure O2 plasma jet can selectively remove the surface contaminants from the TiO2 photocatalytic electrode such as polymer residue and carbon contamination in the TiO2 photocatalytic electrode. The combination of the direct writing technique enables the treatment of a large surface area.